2014
DOI: 10.5539/ijbm.v9n5p184
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Capital Structure on Firm Performance: Evidence from Bangladesh

Abstract: This paper mainly studies the influence of capital structure on firm's performance. This investigation has been performed on a sample of 36 Bangladeshi firms listed in Dhaka Stock Exchange during the period 2007-2012. We have used four performance measures; earnings per share (EPS), return on equity (ROE), return of asset (ROA) and Tobin's Q; as dependent variables and three capital structure ratios; short-term debt, long-term debt and total debt ratios; as independent variables. Using pooling panel data regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
74
4
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(118 citation statements)
references
References 26 publications
29
74
4
11
Order By: Relevance
“…However, it contradicts with the findings of Khatab et al [34] whose findings have shown an insignificant relation between profitability and firm size. Positive relation between growth and profitability found in this study is consistent with studies by: Chowdhury and Chowdhury [4]; Hasan et al [13]; Zeiun and Tian [19]; and, Sharma and Handoo [35].…”
Section: Discussion Of the Findingssupporting
confidence: 82%
See 1 more Smart Citation
“…However, it contradicts with the findings of Khatab et al [34] whose findings have shown an insignificant relation between profitability and firm size. Positive relation between growth and profitability found in this study is consistent with studies by: Chowdhury and Chowdhury [4]; Hasan et al [13]; Zeiun and Tian [19]; and, Sharma and Handoo [35].…”
Section: Discussion Of the Findingssupporting
confidence: 82%
“…However, no one optimal capital structure could be determined, as profitability and capital structure tend to vary for firms: operating in different industry; of variable size; and, operating in diverse economies [7]. Bali (Indonesia) Jan. [12][13]2018 Even though extensive empirical research has been conducted to study the relationship between capital structure and firm performance, little research has focused on IT industry and even less on Bangladesh. Therefore, the objective of this paper is to examine the capital structure determinants affecting the profitability of IT companies in Bangladesh, by using a sample of five IT companies listed in the Dhaka Stock Exchange for the period 2007-2015.…”
Section: Background Of the Studymentioning
confidence: 99%
“…The insignificant relationship between the STDR and accounting based measure which is ROA indicates that STDR has no significant impact on returns of construction firms in Malaysia. This result is consistent with the study by Ebrati, Emadi, Balasang, and Safari (2013), Hamid, Abdullah, and, Kamaruzzaman (2015), Hasan, Ahsan, Rahaman, and Alam (2014), Khan (2012), Olokoyo (2013), andTaani (2013). Table 2 also shows that the relationship between LTDR and ROA in construction firms in Malaysia is not statistically significant (LTDR: β = -1.6402, p > 0.05).…”
Section: Capital Structure and Return On Assetsupporting
confidence: 81%
“…Thirdly, Salim and Yadav (2012) used Pooled Ordinary Least Square (POLS) method to analyse their data which is generally known that the method are unable to control the individual or time-specific effect or in another term is called unobserved effect (Hasan et al, 2014;Manawaduge, Zoysa, & Chowdhury, 2011;and Seetanah, Seetah, Appadu, & Padachi, 2014). Thus, this will allow heterogeneity bias to occur that arise due to the omitting a time constant variable (Wooldridge, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation